Exons encode functional and structural units of chicken lysozyme. - Jung, A (1980)
The nucleotide sequence was determined for the chicken egg white lysozyme mRNA and for the exons of the gene together with their flanking intron regions. The exon pattern is to some degree related to the structural subdivision of the final protein product. However, the relationship of exons to functional units of the enzyme is better established. Exon 2 codes for amino acids 28-82, which include the catalytically active residues and a cluster of amino acids which bind rings C, D, E, and F of the oligosaccharide substrate. Exon 3 codes for amino acids 82-108, which give additional substrate specificity, determine the cleavage frame for the alternating N-acetylglucosamine/N-acetylmuramic acid chain, and increase the catalytic efficiency of the active center. Exons 1 and 4, respectively, code for translational signal sequences on the mRNA, for the signal peptide of prelysozyme, and for the amino- and carboxy-terminal regions of the enzyme. These regions increase the stability of the molecule but are not directly involved in the catalytic function.